Analisis kemampuan pemecahan masalah dan self-efficacy menggunakan model problem-based learning di SMK Negeri 1 Patumbak - Rahmadani, Rizki; Nurdalilah, Nurdalilah (Journal of Didactic Mathematics, 2023)
The purpose of the research conducted by the author was to describe problem-solving abilities and self-efficacy using the problem-based learning model conducted in class X students of SMK Negeri 1 Patumbak on statistics. The type of research used in this research is qualitative research with a descriptive approach. In this study, data was collected through the administration of problem-solving written tests, questionnaires and interviews. The results of this study are that after applying the problem-based learning learning model conducted in class X PPLG 1 SMK Negeri 1 Patumbak it has a good impact on problem-solving abilities and students' self-efficacy in statistical material, the percentage results in problem-solving abilities are 91.94% with very high category , then on students' self-efficacy after applying the problem-based learning model is 80,24% with a very strong category, and students show good responses to problem-based learning with an average of 80,83%. After applying the problem-based learning model to statistics mathematics learning material can make students' self-efficacy better and stronger, the problem-based learning model is very good to use in mathematics learning statistics material.